The Formation of Abhekteh (Devotional) Character In Children In Family Care of Kyai Madura - Aziz, Thorik; Ardhana Reswari; Ria Astuti; Fadilah; Denok Dwi Anggraini; Rasidi; Devi Kurnia Rahmawati (Institut Agama Islam Negeri Madura, 2025)
This study aims to examine the formation of the character